Colour detection device: article / Nor Izzati Ishak - Ishak, Nor Izzati (2013)
This colour detection device is designed to help the blind people in identifies the colour of objects to recognize the four basic colours and speak the recognized colour. This project is one of the alternatives for use by vision-impaired people to allow them to perform basic colour recognition tasks and to handle their problem relies on colours to enjoy their activities and do the tasks or perform their jobs. This project uses a red, green, blue and yellow LED to illuminate a surface. The intensity of reflected light from each colour is measured with a photoresistor (LDR). The operation of the system is controlled by an Arduino Uno R3 microcontroller and the determined colour is spoken through an Emic 2 Talk-toSpeech module. This project is one of the ways to help the blind people’s life simpler and practical in which they can be supported to lead independent and fulfilling lives.